Genetic Improvement of Jatropha curcas (L.) Possibilities and Prospects - Sujatha, M. (Indian Journal of Agroforestry, 2020)
Jatropha curcas, a drought perennial shrub has evoked interest all over the world as potential petrocrop. Programmes launched in several countries for introduction of the crop for varied purposes met with limited success owing to no or low fruit yields in the established plantings. The wide gap in potential and actual yields is due to the use of locally available ’wild’ material. The limitations with the currently used germplasm in India are the lack of knowledge of the genetic base, poor yields, low genetic diversity and vulnerability to a wide array of insect pests and diseases under monoculture. The crop has not been domesticated so far and there is an urgent need to initiate systematic breeding programmes for breeding superior high yielding genotypes in order to avoid long lasting disappointment, frustration and mistrust among the stakeholders. Vast scope lies for genetic improvement of the crop through use of mutation techniques and interspecific hybridization. Mutation breeding can aid in bringing gross changes in plant architecture. Interspecific hybridization with sexually compatible species facilitates introgression of desirable characters, such as, high oil content, oil quality, resistance to insect pests and diseases, reduced toxicity and improved growth on problematic sites. Jatropha species are amenable to tissue culture manipulations, which indicate scope for widening the genetic base through parasexual hybridization and biotechnological tools.